Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fphar.2018.00616
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Analysis Reveals the Potential Mechanisms of Three Bioactive Ingredients of Fufang E’jiao Jiang During Chemotherapy-Induced Myelosuppression in Mice

Abstract: Although multiple bioactive components have been identified in Fufang E’jiao Jiang (FEJ), their hematopoietic effects and molecular mode of action in vivo are still not fully understood. In the current study, we analyzed the effects of martynoside, R-notoginsenoside R2 (R2), and 20S-ginsenoside Rg2 (Rg2) in a 5-fluorouracil-induced myelosuppression mouse model. Bone marrow nucleated cells (BMNCs) counts, hematopoietic progenitor cell colony-forming unit (CFU) assay, as well as flow cytometry analysis of Lin-/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Notoginsenoside R2 (NGR2) is an active saponin molecule extracted from the root of PN. Previous studies showed that it reduced A25-35-induced neuronal apoptosis and inflammation (8), and stimulated the growth of bone marrow nucleated cells and hematopoietic stem cells, as well as burst-forming unit-erythroid and colony-forming unit granulocyte-monocyte colony expansion (9). However, the role of NGR2 in angiogenesis remains unexplored, which is precisely the purpose of this study.…”
Section: Introductionmentioning
confidence: 84%
“…Notoginsenoside R2 (NGR2) is an active saponin molecule extracted from the root of PN. Previous studies showed that it reduced A25-35-induced neuronal apoptosis and inflammation (8), and stimulated the growth of bone marrow nucleated cells and hematopoietic stem cells, as well as burst-forming unit-erythroid and colony-forming unit granulocyte-monocyte colony expansion (9). However, the role of NGR2 in angiogenesis remains unexplored, which is precisely the purpose of this study.…”
Section: Introductionmentioning
confidence: 84%
“…Thereby, discerning miRNAs, related targets genes, and their regulatory signaling pathways are crucial in knowing the common biological development of miRNAs and their actions in the disease process ( Croce, 2009 ; Liu et al, 2014 ). Nowadays, scientists have explored the traditional Chinese Medicine (TCM) pharmacological mechanism and potential therapeutic targets via transcriptomics technologies ( Zhang et al, 2017b ; Xu, 2017 ; Li et al, 2018 ). miRNA-based therapeutics approaches have been assessed at the preclinical and clinical stages.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the body weights, the levels of blood routine indicators like HCT, HGB, and RBC, the thymus and spleen indexes, and the serum levels of hemopoietic growth factors, including IL-3, GM-CSF, and M-CSF, were adopted to evaluate the hematopoietic function [ 37 , 38 ]. FEJ is a well-known and clinically effective proprietary Chinese medicine for the treatment of BD and therefore its clinical dose was used in the positive control of this study [ 39 ]. The observation and body weights of mice were only general indicators, the efficacies of blood tonic should be assessed primarily by reference to the data of blood routines.…”
Section: Discussionmentioning
confidence: 99%